Auditoría de gestión y su incidencia en el área de talento humano de la escuela de conducción del sindicato cantonal de choferes profesionales de Valencia, año 2013 - Zambrano Figueroa, Andrea Vanessa (2015)
This thesis entitled "Management Audit and its impact on the area of Human Talent cantonal Driving School Professional Drivers' Union of Valencia, 2013," has four objectives listed below: analyze the level of compliance selection policies, training, promotion and incentives of personnel working in the institution, to evaluate the influence of internal control in institutional work environment, establish the confidence level of internal procedures by management indicators in the area of human talent institution to issue a final audit report to the area of human talent of the Cantonal Union of Professional Drivers of Valencia. This project has scientific foundations that were taken from authors that deal with the topic of study in order to find theories, concepts, articles, definitions. For this project methods, techniques and types of research which helped in achieving the objectives were used. The results obtained in the development of research reflect the following: that the level of compliance with the policies of selection, training, promotion and incentives of personnel working in the institution, are not being met, while in another aspect 100% meets the stated objectives in terms of functions, they are developed according the professional profile, he results of the assessment of the level of influence of internal control regarding the working environment is favorable according to 87% of employees the institution, and the first element of COSO II refers to the control environment shows that the reliability of this indicator is 66.67%, management indicators showed a confidence level of internal procedures, of effectiveness of 83.34%, so that the efficiency is 100% and the risk level of efficiency is 33.33%, this clearly shows that there is a level over the reliability of corporate goals, it was possible to issue a final report, where the findings obtained during the investigation were analyzed, this information will allow the authorities of the institution to take necessary precautions.